Kinematics of the Kashmir Himalaya: Inferences from geological and geodetic data - Ahsan Afzal Wani; Bikram Singh Bali; Sareer Ahmad Mir; Mohammad Irfan Wani (Geodesy and Geodynamics, 2025)
The GPS data sourced from the permanent GPS network in the Kashmir Himalaya were utilized to quantify both vertical and horizontal deformation rates in the Kashmir Valley of the northwestern Himalaya. While lateral deformation in the Kashmir basin has been previously quantified, the vertical component has not been studied yet. To quantify the vertical and horizontal deformation rates in the Kashmir Valley, we use GAMIT/GLOBK software to process the GPS data. The lateral motion data indicate that the Indian plate continues to move towards the Eurasian plate at a rate of 36–42 mm/yr, while the vertical vectors infer a transition zone across the Kashmir valley.Using ArcGIS, Iso-base and Iso-ketabase maps were generated from the GPS vertical vectors to study the vertical deformation status of the Kashmir Valley. The analysis of vertical vectors reveals a significant transition zone in the Kashmir Valley. The vertical vector data show distinct patterns: GPS stations in the northeast, south, and southeast of the Kashmir Valley exhibit uplift, while stations in the north, northwest, and southwest show subsidence. The uplift velocity increases as we move from the Srinagar station to the Kulgam station via Tral and Ashmuqam, while the subsidence rate increases as we move from the Bandipora station to Mulgam and Uri. Specifically, the highest uplift rate (5.2 ± 0.6 mm/yr) is observed at the Kulgam station and the highest subsidence rate (−6.5 ± 1.26 mm/yr) at the Uri station. On average, vertical subsidence of −2.81 mm/yr is recorded along the north and northwest sides of the valley, and an average uplift of 3.04 mm/yr in the south and southeast.Integrating geomorphological observations with GPS measurements, we infer the presence of an active normal fault running northeast-southwest across the Kashmir Valley, transverse to the major thrust faults. Recent seismic events, including the MW3.9 event near Nagbal and the MW3.7 event near Mujgund in 2020, clustering of local seismic events, and two devastating historical seismic events (1828 AD and 1877/1878 AD) along this transition zone highlight the fault's activity and the region's vulnerability to future earthquakes. Delineation of such geological structures is crucial for seismic hazard assessment and micro-seismic zonation in the Kashmir Valley. Therefore, this study represents a significant step towards understanding the geodynamics and kinematics of the region and improving seismic risk mitigation strategies.